Business Process Assessment with Balanced Scorecard and Framework COBIT - Harryston Nagata; Johanes Fernandes Andry (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
Manufacturing company is the company that produces household appliances based on plastic / plastic houseware, this company has applied information system but there is often problem in sales department that is when processing of data discount, data obtained wrong and not according to which have been determined. Therefore, the author is given the task to audit the information system on the company. The author uses the COBIT and Balance Scorecard framework, the COBIT domain used is the Plan and Organize (PO) and Acquire and Implement (AI), in the PO Domain the author uses PO4 sub-domains (Define the IT Processes, Organization and Relationships) Communications management aims and direction) and PO 9 (Assess and Manage IT risks) whereas in AI Domain used is AI4 (Enable Operation and Use), Balanced Scorecard Perspective used in this research is Internal Business Process, which focuses on business process assessment company and business goals have been in line with IT goals. The results from this research is still many deficiencies that exist in company especially at risk management of IT proven and IT risk management that have not managed maximally so that can be developed in the future.